Universal Alienation - David Harvey (tripleC: Communication, Capitalism & Critique, 2018)
This article is part of a debate between David Harvey, Michael Hardt and Toni Negri. It takes Marx’s bicentenary as occasion for an update of his concept of alienation. The paper asks: how are we to interpret universal alienation and from whence does it come? Marx radically reformulated the concept of alienation in the Grundrisse. The humanism of the early Marx can be re-rooted and reconceptualised in the scientific mode proposed in the Grundrisse. In the Grundrisse, the universality of alienation is specific to capitalism’s historical evolution. Today, alienation exists almost everywhere. It exists at work in production, at home in consumption, and it dominates much of politics and daily life. Such trends intensify through the application of information technologies and artificial intelligence. Widespread alienation has resulted in Occupy movements as well as right-wing populism and bigoted nationalist and racist movements. Donald Trump is the President of alienation. The circulation of capital as totality consists of the three key moments of production, circulation and distribution. A lot of contemporary economic struggles are now occurring at the point of realisation rather than at the point of production. Protests are therefore today often expressions of broad-based discontent. Our future is dictated by the need to redeem our debts. Under such conditions democracy becomes a sham. The big question is what forms of social movement can help us get out of the state-finance nexus. The theory of objective alienation along with an understanding of its subjective consequences is one vital key to unlock the door of a progressive politics for the future.